DETERMINATION OF EXTREME VALUES OF REACTIONS IN KINEMATIC COUPLES OF A TURNING MACHINE IN WHICH THE CAPACITY PERFORMS COMPLEX SPATIAL MOVEMENT - ZALYUBOVSKYI, MARK; PANASYUK, IGOR; KOSHEL, OLEXANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Technological operations of felting can be performed using various equipment. The most intensive technological process is implemented with the use of rolling machines, in which working containers perform complex spatial movement. To date, various types of such machines with individual structural and technological features have been developed, which, with high productivity, ensure the performance of various felting technological operations, in particular - grinding, polishing or glossing, strengthening of the surface layer of parts, separation from sprues or mixing of substances. From a structural point of view, machines with complex spatial movement of the container are complex spatial mechanisms, in the vast majority, with rotational kinematic pairs. An important aspect of the long-lasting and trouble-free operation of such machines is the proper design of kinematic pairs, taking into account the reactive loads that arise during the operation of the machines. Thus, using CAD "SolidWorks", 3D modeling of the rolling structure of the machine with an additional moving link connecting rod with two rotational kinematic pairs, in which the capacity performs complex spatial movement, with subsequent determination of the reaction in all rotational kinematic pairs depending on the change in the interaxial distance of the working capacity, was carried out. As a result of the conducted research, the relationship between the change in the interaxial distance of the container and the extreme values of the reactions that will occur in the rotational kinematic pairs has been established. The obtained results of analytical studies can be useful at the stage of designing similar felting equipment.
Keywords: kinematic pairs; reactions; capacity; spatial motion